Perivascular Epithelioid Cell Tumor of the Ileum Presenting as Diverticulitis - Saime Unluoglu; Umit Bayol; Nilay Korkmaz; Bekir Ozenen; Fuat Ipekci; Emel Ebru Pala (Case Reports in Pathology)
Perivascular epithelioid cell tumors (PEComas) are a group of rare mesenchymal neoplasms. Gastrointestinal PEComas are exceptionally rare, there being only a few case reports in the literature involving the colon and small intestine. Nearly all PEComas show immunoreactivity for both melanocytic (HMB45 and/or Melan-A) and smooth muscle (actin and/or desmin) markers. A 36-year-old male was admitted to the hospital with acut- abdomen. At laparatomy, a nodular mass protruding from the ileum which clinically simulated a diverticulitis was noticed. Gross examination of the specimen revealed a 2×1,5×1 cm secondarily ulcerated, solid, nodular, gray white tumor mass in the ileal wall. Histologically, tumor cells were composed of nests of round-polygonal epithelioid cells with abundant clear to slightly eosinophilic granular cytoplasm and round vesicular nuclei. The nests were separated by thin fibrovascular septa. Minimal necrosis and low mitotic activity were noticed in the tumor. Immunohistochemically, tumor cells were positive for SMA, HMB45, and Melan-A and negative for CD10, RCC, CD45, CD117, CD34, EMA, and Desmin. Diagnosis was PEComa of the ileum. We report the case of ileal PEComa to remind the unusual presentation (diverticulitis) of these tumors, besides rarity and diagnostic difficulties.